Legalização da prostituição - DURAN, Juliana Nascimento (2021)
Since the dawn of creation, the activity of prostitution was viewed with a bad eye and that continues to this day. Its practice is full of discrimination, moralism, prejudice and repudiation. Although many people use this practice for their survival, there is still no favorable consensus about it. Thus, prostitution is totally excluded from jurisdictional protection, concatenating itself by normative omission, contributing to marginalization, consequent violation of fundamental rights and inevitably, by the loss of human dignity. The present work (which materializes through theoretical means), aims to highlight some important points regarding the practice of prostitution, related to the dignity of the human person. Although prostitution has been recognized by the Ministry of Labor as a profession since 2002 and there is already a Bill n° 4,211/2012, entitled Gabriela Leite Bill, authored by Federal Deputy Jean Wyllys, the problem is still very far from be recognized and respected as decent work.